Algebrismo e o ensino de funções: uma proposta didática para a Educação de Jovens e Adultos - Rezende Filho, Carlos Antonio (2020)
The present work of qualitative nature aims to present reflections on Malba Tahan's pedagogical speech about algebraism and its combat. It uses his criticism to current algebra teaching, in order to elaborate a didactic proposal, that could help in the concept of function for the first year of high school for Youth and Adult Education modality, contributing to the specificities of this modality. To do so, a part of Professor Mello and Souza´s life and work is presented, in order to make use of his pedagogical discourse against algebraism. Later, a discussion about Youth and Adult Education takes place, presenting part of its historical path in Brazilian education, aiming to identify the specificities of this teaching modality and its target audience. This way, a didactic proposal, which is the educational product resulting from this research, was elaborated. It was based on the combat of algebraism and in favorable atmosphere to mathematical learning (D 'AMBROSIO, 1993), that can help in the construction of the concept of polynomial functions of the first degree. Due to the pandemic of the new Coronavirus, the proposal could not be applied in the first year classes of Youth and Adult Education modality. An alternate way found for dialogue and analysis of the didactic proposal was the application of questionnaires for their leading teachers, in the schools of Ituiutaba - MG. Thus, after the teachers´ educational product analysis, a questionnaire was applied in order to collect the pedagogical speeches about the elaborated material. For the analysis process, we used three emerging categories, in order to triangulate the data, theoretical contributions, didactic proposal and the pedagogical speeches of the interviewed teachers. It is pointed out that the elaborated product can be considered a way to the teaching of the concept of functions for first year classes, Youth and Adult Education modality, since the scenarios, presented and analyzed, consider their specificities and focus on the content in a contextualized way.